Nano‐therapeutic strategies to target coronavirus. Issue 3 (9th March 2021) - Rauf, Mohd Ahmar; Tasleem, Munazzah; Bhise, Ketki; Tatiparti, Katyayani; Sau, Samaresh; Iyer, Arun K.
Abstract: The coronaviruses have caused severe acute respiratory syndrome (SARS), the Middle East respiratory syndrome (MERS), and the more recent coronavirus pneumonia (COVID‐19). The global COVID‐19 pandemic requires urgent action to develop anti‐virals, new therapeutics, and vaccines. In this review, we discuss potential therapeutics including human recombinant ACE2 soluble, inflammatory cytokine inhibitors, and direct anti‐viral agents such as remdesivir and favipiravir, to limit their fatality. We also discuss the structure of the SARS‐CoV‐2, which is crucial to the timely development of therapeutics, and previous attempts to generate vaccines against SARS‐CoV and MERS‐CoV. Finally, we provide an overview of the role of nanotechnology in the development of therapeutics as well as in the diagnosis of the infection. This information is key for computational modeling and nanomedicine‐based new therapeutics by counteracting the variable proteins in the virus. Further, we also try to effectively share the latest information about many different aspects of COVID‐19 vaccine developments and possible management to further scientific endeavors. Abstract : The role of nanotechnology in the detection and the therapeutics of the COVID‐19. The image was created with biorender.com.